2015
DOI: 10.1089/jwh.2014.4857
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Events During Pregnancy and Postpartum Depressive Symptoms

Abstract: Background: Understanding the influence of perinatal stressors on the prevalence of postpartum depressive symptoms (PDS) and help-seeking for PDS using surveillance data can inform service provision and improve health outcomes. Methods: We used Massachusetts Pregnancy Risk Assessment Monitoring System (MA-PRAMS) 2007-2010 data to evaluate associations between selected perinatal stressors and PDS and with subsequent help-seeking behaviors. We categorized 12 stressors into 4 groups: partner, traumatic, financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 61 publications
11
57
0
1
Order By: Relevance
“…Indeed, postpartum depression represents one of the most common complications following childbirth and has been estimated to affect up to 20% of new mothers (O’Hara and McCabe, 2013; Wisner et al, 2013; Agrati and Lonstein, 2015; Brummelte and Galea, 2015). A number of factors have been identified that may increase the risk of postpartum depression (Robertson et al, 2004; Stone et al, 2015), including stress during pregnancy and/or after birth which can be easily modeled in rodents (Perani and Slattery, 2014). For example, a growing body of research has revealed that repeated exposure to stress while pregnant can induce behavioral despair and impaired maternal care during the postpartum period (Smith et al, 2004; O’Mahony et al, 2006; Haim et al, 2014; Leuner et al, 2014), thus acting as a model of postpartum depression.…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
“…Indeed, postpartum depression represents one of the most common complications following childbirth and has been estimated to affect up to 20% of new mothers (O’Hara and McCabe, 2013; Wisner et al, 2013; Agrati and Lonstein, 2015; Brummelte and Galea, 2015). A number of factors have been identified that may increase the risk of postpartum depression (Robertson et al, 2004; Stone et al, 2015), including stress during pregnancy and/or after birth which can be easily modeled in rodents (Perani and Slattery, 2014). For example, a growing body of research has revealed that repeated exposure to stress while pregnant can induce behavioral despair and impaired maternal care during the postpartum period (Smith et al, 2004; O’Mahony et al, 2006; Haim et al, 2014; Leuner et al, 2014), thus acting as a model of postpartum depression.…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
“…The occurrence of stressors during the lifespan has been described as an important risk factor for depressive disorders [51,52], including peripartum depressive episodes [53,54]. The CRHR1 polymorphisms seem to modulate the sensitivity to stress, probably through their role in the regulation of HPA axis function, increasing the risk of depression [29,55]; but, unfortunately, our data do not allow us to establish causal relationships.…”
Section: Implications Of Polymorphisms In the Crhr1 Gene On The Hypotmentioning
confidence: 60%
“…Studies suggest it is relatively common for pregnant women to report the experience of stressful life events (Brown et al, 2011, Meijer et al, 2014, Stone et al, 2015. In a large, randomly selected sample of women, 17.0% reported having three or more stressful life events in the one year prior to their baby's birth .…”
Section: Adversity In Pregnancymentioning
confidence: 99%